2019
DOI: 10.1111/1744-7917.12667
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression of sensory neuron membrane proteins in the parasitoid Microplitis mediator (Hymenoptera: Braconidae)

Abstract: Sensory neuron membrane proteins (SNMPs), homologs of the human fatty acid transport protein CD36 family, are observed to play a significant role in chemoreception, especially in detecting sex pheromone in Drosophila and some lepidopteran species. In the current study, two full-length SNMP transcripts, MmedSNMP1 and MmedSNMP2, were identified in the parasitoid Microplitis mediator (Hymenoptera: Braconidae). Quantitative real-time polymerase chain reaction analysis showed that the expression of MmedSNMP1 was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 66 publications
(113 reference statements)
2
21
0
Order By: Relevance
“…Insect SNMPs play important roles in signal transduction. MmedSNMP2 from M. mediator is not only expressed in antennae, but also in head, legs and other tissues, suggesting the multiple roles of MmedSNMP2 (Shan et al, 2019). AlucSNMP2a identified in legs of A. lucorum may participate in multiple ecological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Insect SNMPs play important roles in signal transduction. MmedSNMP2 from M. mediator is not only expressed in antennae, but also in head, legs and other tissues, suggesting the multiple roles of MmedSNMP2 (Shan et al, 2019). AlucSNMP2a identified in legs of A. lucorum may participate in multiple ecological functions.…”
Section: Discussionmentioning
confidence: 99%
“…SNMP1s have originally been discovered as proteins specific to OSNs of pheromone-sensitive sensilla in the moth Antheraea polyphemus (Rogers et al 1997 ). Accordingly, ISH and IHC investigations of SNMP1 orthologues in other moths (Rogers et al 2001a , Forstner et al 2008 , Gu et al 2013 , Liu et al 2014 ), as well as in flies (Benton et al 2007 ), wasps (Shan et al 2020 ), and locusts (Pregitzer et al 2017 , Pregitzer et al 2019 ), revealed their neuronal expression in OSNs of the antenna.…”
Section: Expression Of Snmps In the Olfactory System And Beyondmentioning
confidence: 99%
“…SNMP1 of D. melanogaster is involved in pheromone detection and enhances the Ca 2+ responses served in signal transduction 76 . SNMP1 of M. mediator was determined to participate in both pheromone and general odor detection 77 . In contrast, the general functional mechanism of SNMP2 in parasitoids is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%